2018
DOI: 10.1101/477034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontal and parietal alpha oscillations reflect attentional modulation of cross-modal matching

Abstract: Multisensory perception is shaped by both attentional selection of relevant sensory inputs and exploitation of stimulus-driven factors that promote cross-modal binding. Underlying mechanisms of both top-down and bottom-up modulations have been linked to changes in alpha/gamma dynamics in primary sensory cortices and temporoparietal cortex. Accordingly, it has been proposed that alpha oscillations provide pulsed inhibition for gamma activity and thereby dynamically route cortical information flow. In this study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…However, modulations in low beta over sensory regions have also been reported during attentional tasks (e.g., van Ede, Koster, and Maris (2012) and Siegel et al (2008)). Moreover, a modulation in a similar frequency range (10–20 Hz) in and between nodes of the VAN and DAN has been reported during a visual search task (Spaak, Fonken, Jensen, & de Lange, 2016) as well as in anticipation of or during the processing of matching stimuli in multisensory paradigms (Goschl, Friese, Daume, Konig, & Engel, 2015; Misselhorn, Friese, & Engel, 2019; Wang, Goschl, Friese, Konig, & Engel, 2019). Interestingly, a comprehensive study has demonstrated that alpha‐beta frequency peaks differ across regions and experimental designs (Haegens, Cousijn, Wallis, Harrison, & Nobre, 2014) (see also ElShafei et al (2018)).…”
Section: Discussionmentioning
confidence: 64%
“…However, modulations in low beta over sensory regions have also been reported during attentional tasks (e.g., van Ede, Koster, and Maris (2012) and Siegel et al (2008)). Moreover, a modulation in a similar frequency range (10–20 Hz) in and between nodes of the VAN and DAN has been reported during a visual search task (Spaak, Fonken, Jensen, & de Lange, 2016) as well as in anticipation of or during the processing of matching stimuli in multisensory paradigms (Goschl, Friese, Daume, Konig, & Engel, 2015; Misselhorn, Friese, & Engel, 2019; Wang, Goschl, Friese, Konig, & Engel, 2019). Interestingly, a comprehensive study has demonstrated that alpha‐beta frequency peaks differ across regions and experimental designs (Haegens, Cousijn, Wallis, Harrison, & Nobre, 2014) (see also ElShafei et al (2018)).…”
Section: Discussionmentioning
confidence: 64%
“…ERD may be particularly suited for the type of naturalistic stimuli used here (i.e., environmental sounds), as identification of these sounds may be protracted in time and poorly synchronized across participants. We expected greater frontal and occipital alpha ERD for voluntary than involuntary retrieval across both age groups, reflecting increased effortful control (Misselhorn et al., 2019; Parvaz et al., 2012) and external attention (Klimesch, 2012) associated with intentional retrieval. Furthermore, we expected voluntariness to interact with age such that older adults may show greater frontal alpha ERD than younger adults in the involuntary condition, possibly reflecting frontal overactivation at lower levels of demand (e.g., Cappell et al., 2010; Grady, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…In addition to these oscillation‐based memory effects, alpha ERD has also been linked more generally to cortical activation (Klimesch, 2012; Klimesch et al., 2007). Alpha ERD at frontal sites is thought to reflect activation of frontal control processes, including executive control, directed attention, and effortful cognitive reappraisal (Klimesch, 2012; Misselhorn et al., 2019; Parvaz et al., 2012; Tschentscher & Hauk, 2016). At occipital sites, alpha ERD has been associated with attention using visual stimuli (Pfurtscheller et al., 1994), as well as in a modality‐independent manner (Peng et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An increased frontal alpha amplitude may enable a tight functional coupling between frontal cortical areas, thereby allowing the control of the visual processing [40]. Alpha oscillations of frontal brain areas seem to be important for the top-down control [41,42]. A recent simultaneous EEG-fMRI study further found that long-range alpha synchrony was intrinsically linked to activity in the frontal-parietal control network [43].…”
Section: Plos Onementioning
confidence: 99%